2011
DOI: 10.1088/2043-6262/2/4/043001
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion protection with eco-friendly inhibitors

Abstract: Corrosion occurs as a result of the interaction of a metal with its environment. The extent of corrosion depends on the type of metal, the existing conditions in the environment and the type of aggressive ions present in the medium. For example, CO 3 −2 and NO −3 produce an insoluble deposit on the surface of iron, resulting in the isolation of metal and consequent decrease of corrosion. On the other hand, halide ions are adsorbed selectively on the metal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 43 publications
0
15
0
4
Order By: Relevance
“…The importance of corrosion damage in reinforced concrete structures has led to applications in this field, showing the potential in qualitative analysis (e.g., [17,20,31,32]). Several studies have shown a significant decrease in the amplitude of the GPR reflected wave in parts of the radar images [17].…”
Section: Gpr Fundamentals In the Detection Of Corrosionmentioning
confidence: 99%
“…The importance of corrosion damage in reinforced concrete structures has led to applications in this field, showing the potential in qualitative analysis (e.g., [17,20,31,32]). Several studies have shown a significant decrease in the amplitude of the GPR reflected wave in parts of the radar images [17].…”
Section: Gpr Fundamentals In the Detection Of Corrosionmentioning
confidence: 99%
“…Several researchers proposed mechanism of steel corrosion in concrete (Shahid, 2011;Jae et al, 2016;Cabrini et al, 2015;Elsener, 2001;Söylev, 2008;Ormellese et al, 2006;Page, 1975;Hausmann, 1967;Gouda, 1970;Valcarce, 2008;Freire, et al, 2009;Cabrini, 2002;Asma et al, 2011). All agree that corrosion on rebar is influenced by properties of concretes.…”
Section: Corrosion Mechanism Of Steel Rebarmentioning
confidence: 99%
“…When applying inhibitors, the most adaptable technique for investigating corrosion kinetics is potentiodynamic polarization. Figure (1) shows anodic and cathodic polarization of the mild steel in sulfuric acid solutions with and without the addition of different concentrations of LU. The figure shows that as the inhibitor concentration increases, the corrosion current decreases.…”
Section: Potentiodynamic Polarizationmentioning
confidence: 99%
“…Sulfuric acid is one of the most difficult common acids to handle when considering corrosion. There are various organic inhibitors that decrease the corrosion rate of mild steel in acidic solutions [1] . The efficiency of an organic inhibitor is mainly dependent on its ability to be adsorbed on the metal surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation